The Fog of War: Prosecuting Illegal Uses of Force as Crimes Against Humanity - Manuel J. Ventura; Matthew Gillett (Washington University Global Studies Law Review, 2013)
This Article considers the possibility of the prosecution of aggression as a crime against humanity before the International Criminal Court (“ICC”). First, it explores the constitutive elements of crimes against humanity and compares them to those of the crime of aggression. In doing so, it identifies a number of areas where aggression will assist in establishing critical elements required to sustain a conviction for crimes against humanity. Second, it presents a legal strategy whereby aggression can be adjudicated as an element of co-perpetration as a mode of liability when prosecuting crimes against humanity. In this manner, a factual finding that aggression has been committed can be made without entering a conviction per se for the crime. Such a finding can then be considered at sentencing either as an aggravating factor or as indicative of the gravity of the crimes and could ultimately result in the imposition of a longer custodial sentence. Thus, whilst the ICC may not currently possess jurisdiction ratione materiae over aggression, this should not limit the ability of ICC prosecutors to substantively invoke the crime where crimes against humanity are committed as a result of the illegal use of armed force.
Keywords: aggression; use of force; crimes against humanity; international criminal court; ICC